11th hour - Patterson, James, 1947-; Paetro, Maxine (New York : Little, Brown and Co., 2012)
When millionaire Chaz Smith is mercilessly gunned down, Lindsay Boxer discovers that the murder weapon is linked to the deaths of four of San Francisco's most untouchable criminals. Then she's called next to the most bizarre crime scene she's ever witnessed: two bodiless heads elaborately displayed in the garden of a world-famous actor.
English language and literature.
Keywords: Women detectives -- California -- San Francisco -- Fiction; Murder -- Investigation -- Fiction; Police corruption -- Fiction; Man-woman relationships -- Fiction; Suspense fiction; Mystery fiction